Pulse current gas metal arc welding : characteristics, control and applications - Ghosh, Prakriti Kumar (Springer, 2017)
This monograph is a first-of-its-kind compilation on high deposition pulse current GMAW process. The nine chapters of this monograph may serve as a comprehensive knowledge tool to use advanced welding engineering in prospective applications. The contents of this book will prove useful to the shop floor welding engineer in handling this otherwise critical welding process with confidence. It will also serve to inspire researchers to think critically on more versatile applications of the unique nature of pulse current in GMAW process to develop cutting edge welding technology.
Keywords: Gas metal arc welding.; elektronické knihy; electronic books